Correspondence, Glynn County, 1875 - State of Georgia, Glynn County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1875)
Correspondence, Glynn County, 1875. Correspondence regarding deed and tax receipts, Glynn County, 1870. Two land tax receipts and a handwritten Correspondence. Names and details illegible. Clerks Office, Superior Court, Glynn County, Brunswick, Ga., October 7, 1875. 3 pages.
Keywords: Glynn County (Ga.); Deeds; Records and correspondence; Court records